2014
DOI: 10.1007/s12094-014-1253-z
|View full text |Cite
|
Sign up to set email alerts
|

CMTM5 is reduced in prostate cancer and inhibits cancer cell growth in vitro and in vivo

Abstract: These results indicate that CMTM5 is down-regulated in PCa and exhibit tumor suppressor activities in androgen-independent PCa cells. Loss of CMTM5 protein may be contributed to the development of PCa and it is a potential therapeutic target for castration-resistant prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…The growth of ACHN-CMTM5 cells was significantly inhibited, and the cell apoptotic rate was markedly increased, following the transfection of the CMTM5 vector. In addition, it was observed that the restoration of CMTM5 expression suppressed both the motility and invasiveness of ACHN cells, which is in line with previous findings in other tumors (6,7,10,11). In the present study, the ACHN line was selected for functional studies as the CMTM5 mRNA expression level was the lowest of the cell lines tested.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The growth of ACHN-CMTM5 cells was significantly inhibited, and the cell apoptotic rate was markedly increased, following the transfection of the CMTM5 vector. In addition, it was observed that the restoration of CMTM5 expression suppressed both the motility and invasiveness of ACHN cells, which is in line with previous findings in other tumors (6,7,10,11). In the present study, the ACHN line was selected for functional studies as the CMTM5 mRNA expression level was the lowest of the cell lines tested.…”
Section: Discussionsupporting
confidence: 89%
“…However, similarly to the case of CMTM3, no promoter methylation of CMTM5 was observed in RCC cell lines (16). It has been previously indicated that the expression of CMTM5 in multiple other types of tumor was downregulated in RCC mainly by different epigenetic or genetic mechanisms (611). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes at least six mRNA splicing bodies, CMTM5-v1-v6, of which CMTM5-v1 is the most conserved. CMTM5 is widely expressed in many normal tissues such as brain, prostate and small intestine, and has a secretory form [51], although its expression is greatly reduced in many tumor tissues, such as prostate cancer, cervical cancer, ovarian cancer, leukemia, glioma, and digestive system tumors [52][53][54][55][56]. Its anti-cancer mechanism are not clear, but may be related to promoter methylation or the function of multiple signal transduction pathways [11].…”
Section: Cmtm5 and Nsclcmentioning
confidence: 99%
“…Once palpable tumors were formed, tumor growth was monitored as described [14]. There were six mice in the Mock group and six in the CMTM3 group.…”
Section: Tumor Xenograft Model In Nude Micementioning
confidence: 99%